Correlation between Preoperative Cervical CT Values of Hounsfield Units and Height Changes of Adjacent Intervertebral Spaces after Anterior Cervical Discectomy and Fusion - KAIYISAIER· Abudukelimu, LI Lei, YANG Xiaokai, REN Jun, LIU Shuai (Zhongguo quanke yixue, 2023)
Background Preoperative vertebral body Hounsfield units (HU) value measured by routine CT examinations may be associated with loss of adjacent segment height after anterior cervical discectomy and fusion (ACDF) . There are few studies on the relationship between preoperative HU value of the vertebral body and postoperative complications of ACDF. Objective To study the association between preoperative cervical vertebral body HU value and change of upper adjacent segment height after ACDF. Methods A retrospective study of 86 patients diagnosed with cervical spondylotic myelopathy or cervical radiculopathy and treated with single-level ACDF at Department of Spine Surgery, the Sixth Affiliated Hospital of Xinjiang Medical University from January 2017 to January 2021 was conducted. Age, gender, follow-up period, and BMI were all recorded. Preoperative vertebral HU values and Changes in upper adjacent segmental height were measured at 1 week after surgery and the last follow-up time to calculate the values of intervertebral space height loss. Follow-up was till to 2022-02-01. Patients were divided into two groups based on the results of the degeneration of upper adjacent intervertebral space: group A (last follow-up intervertebral space height loss > 20% of the value measured at 1 week postoperatively was defined as upper adjacent intervertebral space degeneration, n=15) and group B (last follow-up intervertebral space height loss < 20% of the value measured at 1 week postoperatively, n=71) . The clinical data between the two groups were then compared. Binary logistic regression analysis was used to investigate the factors influencing the degeneration of upper adjacent intervertebral space. Pearson correlation analysis was used to correlate the preoperative vertebral HU values with the degeneration of upper adjacent intervertebral space. Receiver operating characteristic curve (ROC curve) was plotted for preoperative vertebral CT values to predict postoperative upper adjacent intervertebral space loss in patients. Results There were no significant difference in age, gender, the average follow-up time and BMI between two groups (P>0.05) ; There was a significant difference between the two groups in terms of preoperative vertebral HU values (P<0.05) . Binary Logistic regression analysis showed that low preoperative CT value of cervical vertebra 〔OR=1.05, 95%CI (1.02, 1.08) 〕was a risk factor for upper and adjacent intervertebral space degeneration (P<0.05) . There was a negative correlation between the HU values and upper adjacent segmental height loss (r=-0.844, P=0.001) . Using receiver operating characteristic curves, the area under the curve was 0.830〔95%CI (0.732, 0.928) 〕, and the most appropriate threshold of HU value was 329.17 (sensitivity 71.8%, and specificity 86.7%) . Conclusion Lower preoperative CT HU values are associated with loss of adjacent segment height after single-level ACDF. Preoperative measurement of cervical body HU is useful in predicting the degeneration of upper adjacent intervertebral space after ACDF.